(untitled) (Medico Legal Update, 2021)
The objectives of the study is the assessment of torus palatinus (TP) prevalence as well as torus mandibular is (TM) among different gender and age groups. Seven hundred and fifty (750) out door patients (380 male and 370 female) were tested for the tori presence or absence at dentistry collage in Basrah city between January 2019 and June 2019. Sex, gender and location factors were evaluated. The prevalence rate of TP was 4.73% for male and 5.13% for female, and the prevalence rate of TM was 2.36% for male and 3.24% for female. In females, TP prevalence was more compared to males. The TP incidence more commonly in middle aged persons, While the TM more commonly in older persons.